(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The study aims to identify barriers in the development of social innovation, from the Núcleo Extensionista Rondon (NER-UDESC). In a qualitative approach, interviews and focal groups were performed with actors involved in the project. The results point to various barriers in the development of social innovation, such as the scarcity of financial resources, lack of public engagement, lack of institutional support, limited arrangements, knowledge and communication gaps, resistance to change, and limitations of physical resources of staff. Considering the potential of the NER-UDESC in being an instrument to create lasting connections with the municipalities, enabling university-society integration, this study is expected to help policy-makers in decision-making, stimulating policy development, intersectoral collaborations, and collaborative models for innovation and social welfare.